D’Empires et de frontières. La pratique de la frontière du IXe au XIIIe siècle - Schneider, Jens (Revue belge de philologie et d'histoire, 2013)
Keywords: Territorium

Fleuves, forêts et territoire dans les sources narratives des VIe et VIIe siècles - Guizard-Duchamp, Fabrice (Revue du Nord, 2003)
Abstract: „Through the major narrative sources available for the Gaul area of the vith and viith centuries (Grégoire de Tours, Frédégaire and his followers), the purpose of this paper is first to show in which way rivers and forests contribute to the geographical location of the events reported. The rivers appear essentially as obvious landmarks. Streams and rivers are real obstacles for the progression of armies in campaign. For princes who seek to master the territories of their regnum, the places where land routes cross rivers have a truly strategic importance. However, the rivers are not really considered as territorial limits.“
Keywords: Fluss; Gallien; Territorium; Wald

Les reines mérovingiennes ont-elles une politique territoriale? - Santinelli, Emmanuelle (Revue du Nord, 2003)
Abstract: „If power rests in the Higher Middle Ages first on the control of riches and men, this does not exclude a perception of space. This paper raises the question of the policies led, so as to control and master the territories and the borders, by the Merlovingian queens who held a large share of the authority in the VIth–VIIth centuries (Clotilde, Brunehilde, Frédégonde, Nanthilde, Bathilde). It reveals their intervention in certain successions, privileging sharing or unity, according to the context, the way they manage to spread all over the kingdom bases of operation and relay for the royal authority, and their concern for borders with the strategies they resort to, which do not make them differ really from their male counterparts.“
Keywords: Königin; Macht; Merowinger (Dynastie); Territorium

« Limites sans frontières ». Réflexions sur la perception archéologique de l'espace en Neustrie septentrionale (Ve-VIIIe siècle) - Verslype, Laurent (Revue du Nord, 2003)
Abstract: „The notion of border in the Merlovingian period at the confines of Neustria and northern Austrasia is, in this paper, the object of a strictly archaeological approach. It shows that archaeology often relies on natural geographical, ecclesiastical or cultural limits that undoubtedly define territories, but whose meaning and political fluctuations are but very partially reflected by material sources. The natural environment, the identification of efficient cultural criteria, the occupation of the land, the social and economic interpretation linked with the status of the rural and urban communities don’t allow yet to analyse their relations with real regional territorial entities. In this respect, we believe we can assert that the archaeological analysis of our regions is still carried out on territories with « limits without borders ».“
Keywords: Archäologie; Austrien; Merowinger (Dynastie); Neustrien; Territorium